Glomus patagonicum sp. nov. (Glomerales), a new arbuscular mycorrhizal fungus from Argentina - Novas, María Victoria (2005)
Glomus patagonicum sp. nov. was found in the rhizosphere of Bromus setifolius near El Calafate in Santa Cruz province, Argentina. The species is distinguished by the presence of large ornamented warts on the outer surface of the spore and on the walls of the subtending hyphae. The fungus colonised roots of Lycopersicon esculentum and Trifolium repens and formed Paris-type mycorrhiza.